Wave propagation in undulated structural lattices. (15th October 2016) - Trainiti, G.; Rimoli, J.J.; Ruzzene, M.
Abstract: This work investigates wave propagation in undulated square structural lattices. The undulated pattern is obtained by imposing an initial curvature to the lattice's elements. The study considers both periodic undulated structures, in which the undulation is uniform throughout the structure as well as graded undulated patterns, in which the undulation is modulated within the lattice. Undulation is specifically considered in relation to its ability to induce anisotropy in the equivalent mechanical properties and to break the symmetry of the straight square lattice. Results show that wave motion is inhibited within specified frequency ranges owing to the generation of band gaps, and in specific directions as a result of the undulation-induced anisotropy.